PELATIHAN STRATEGI EMOTION-FOCUSED COPING UNTUK MENURUNKAN TINGKAT STRESS PADA ORANG TUA YANG MEMILIKI ANAK AUTIS - Zahrani Zahrani (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Caring for and raising a child with Autism Disorder is one of the biggest challenges and can cause stress for parents. This research aims to find out whether the emotion-focused coping strategy training provided can reduce stress levels in parents of autistic children at the UPTD for Children with Special Needs, Sidoarjo Regency. This research is a type of qualitative research. The subjects involved were 4 mothers who had autistic children and were detected to have high levels of stress based on the Perceived Stress Scale (PSS). Data collection methods were carried out by observation, in-depth interviews, and providing interventions. The data processing and analysis method consists of data collection, reduction, presentation and drawing conclusions. The research results showed that of the 4 participants who had been given the intervention, there were 3 participants who experienced an increase in their understanding of stress and experienced a decrease in stress levels, while 1 other person could not measure their understanding and changes in stress levels because they did not follow the intervention process to completion. This shows that the emotion-focused coping training carried out in this intervention is effective in reducing stress levels in parents of autistic children at the UPTD for Children with Special Needs, Sidoarjo Regency.